Portable Sequentially Shifted Excitation Raman spectroscopy as an innovative tool for in situ chemical interrogation of painted surfaces. Issue 15 (8th June 2016) - Conti, Claudia; Botteon, Alessandra; Bertasa, Moira; Colombo, Chiara; Realini, Marco; Sali, Diego
Abstract : We present the first validation and application of portable Sequentially Shifted Excitation (SSE) Raman spectroscopy for the survey of painted layers in art. Abstract : We present the first validation and application of portable Sequentially Shifted Excitation (SSE) Raman spectroscopy for the survey of painted layers in art. The method enables the acquisition of shifted Raman spectra and the recovery of the spectral data through the application of a suitable reconstruction algorithm. The technique has a great potentiality in art where commonly a strong fluorescence obscures the Raman signal of the target, especially when conventional portable Raman spectrometers are used for in situ analyses. Firstly, the analytical capability of portable SSE Raman spectroscopy is critically discussed using reference materials and laboratory specimens, comparing its results with other conventional high performance laboratory instruments (benchtop FT-Raman and dispersive Raman spectrometers with an external fiber optic probe); secondly, it is applied directly in situ to study the complex polychromy of Italian prestigious terracotta sculptures of the 16 th century. Portable SSE Raman spectroscopy represents a new investigation modality in art, expanding the portfolio of non-invasive, chemically specific analytical tools.